Nhibitory Property of Poly (AN-co-VP) Copolymer on Some Dermatophyte Fungiand Yeasts Causing Fungal Infections - Sönmez, Pınar Erecevıt; Pıhtılı, Güzin; Torgut, Gulben; Kırbag, Sevda (My University, 2021)
Antimicrobial susceptibility test for poly (AN-co-VP) copolymer, which we think could be an ideal drug in treatment interventions was evaluated with disk diffusion method and minimum inhibitor concentration. In the antimicrobial measurement data, it was determined that the poly (AN-co-VP) copolymer dissolved in pure water is a significant inhibitory property against the growth of yeast (on Candida spp. with 11.33±0.3 mm barrier area) and dermatophyte fungi (on Epidermophyton sp. and Trichophyton sp.with 12.33±0.3 mm barrier area) (p<0.001) and no inhibitory properties were observed in preventing the growth of all bacteria (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, Bacillus megaterium). MIC limit values that prevent the growth of dermatophytes and yeasts supporting the disc diffusion method are 50-100 ?L. This study is an alternative approach in order to limit the spread of superficial fungal infections they cause and eliminate these infections that tend to become chronic since this polymer extract has no inhibitory properties on bacteria but prevents the growth of yeast and dermatophytes.
Keywords: Dermatoloji; Mantar Bilimi; Mikrobiyoloji